THE INFLUENCE OF SYSTEMATIC RISK AND FINANCIAL LEVERAGE TOWARD THE STOCK RETURN OF PHARMACEUTICAL COMPANIES LISTED ON INDONESIA STOCK EXCHANGE IN THE YEAR 2009-2013 - B12111023, MEGA NATALIA (Jurnal Manajemen Update, 2015)
Investor considers risk and return as the important factors in investment. This research was conducted to examine two types of risk factor that influence the stock return, namely systematic risk and financial leverage. In addition, it also considered Economic Value Added (EVA) as the control variable. The population of this research is 10 Pharmaceutical companies listed on Indonesia Stock Exchange in the year 2009-2013 and by purposive sampling the sample size is 7 companies. Data was collected through literature review and documentary studies. Research model uses the panel data technique and multiple regression analysis. Results indicate that systematic risk measured by Beta (Î²) has positive and insignificant influence toward stock return; financial leverage measured by Debt to Equity Ratio has negative and insignificant influence toward stock return; while Economic Value Added (EVA) has the negative and significant influence toward the stock return. Â  Keywords: Stock Return, Systematic Risk, Financial Leverage, Economic Value Added (EVA)